The roles of 3′-exoribonucleases and the exosome in trypanosome mRNA degradation - Fadda, Abeer; Färber, Valentin Lutz Fabian; Droll, Dorothea; Clayton, Christine (RNA, 2013)
The degradation of eukaryotic mRNAs can be initiated by deadenylation, decapping, or endonuclease cleavage. This is followed by 5′-3′ degradation by homologs of Xrn1, and/or 3′-5′ degradation by the exosome. We previously reported that, in African trypanosome Trypanosoma brucei, most mRNAs are deadenylated prior to degradation, and that depletion of the major 5′-3′ exoribonuclease XRNA preferentially stabilizes unstable mRNAs. We now show that depletion of either CAF1 or CNOT10, two components of the principal deadenylation complex, strongly inhibits degradation of most mRNAs. RNAi targeting another deadenylase, PAN2, or RRP45, a core component of the exosome, preferentially stabilized mRNAs with intermediate half-lives. RRP45 depletion resulted in a 5′ bias of mRNA sequences, suggesting action by a distributive 3′-5′ exoribonuclease. Results suggested that the exosome is involved in the processing of trypanosome snoRNAs. There was no correlation between effects on half-lives and on mRNA abundance.
Gesehen am 19.02.2021